The development of Germanic analytical tenses - Botsman, Andriy; Dmytruk, Olga; Kozlovska , Tamara (Current issues of Ukrainian linguistics: theory and practice, 2020)
The stages that encompass the future tense development are singled out as discrete phenomena within the process of the Germanic language development. The Gothic verb system can serve as the background for the investigation of the tense transformations in question. The difficulties of tense examination in the Old Germanic languages were connected with some conceptions about the Indo-Iranian and Greek languages that used to dominate in the scientific circles for a long time. Those conceptions were based on Latin and Greek patterns and postulated the use of present, past and future tenses in all Indo-European languages. The above conceptions were ruined when the study of Tokharian and Hittite demonstrated the use of the present tense for the description of future actions. The idea of losing “the protolanguage inheritance” was proved wrong, and it was incorrect to transfer the complex tense system of Sanskrit, Greek, and Latin to other Proto-Indo-European languages. The examination of the tense differentiation in Gothic (as the main source of the Old Germanic language) demonstrates that the Gothic infinitive functioned as a no-particular-time unit, while personal verb forms were involved in performing tense functions. The Gothic present tense verbs represented present and future tenses and no-particular-time phenomena. Some periphrastic forms containing preterite-present verbs with the infinitive occurred sporadically. The periphrastic forms correlated with Greek and Latin patterns of the same future tense meaning. The periphrastic future forms in Gothic often contained some modal shades of meaning. The Gothic present tense functioned as a colony-forming archi-unit and a pluripotential (temporal) precursor. The periphrastic Gothic future forms are recognised as a monopotential (temporal) precursor with some modal meaning. The key research method used in the present article is the comparative historical method. The authors viewed it as the most reliable and appropriate for the study of tense forms.
Keywords: colony-forming archi-unit, future tense, monopotential precursors, periphrastic forms.